2020
DOI: 10.3389/fmicb.2020.601864
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Decrease in Temperature Increases mcy Gene Transcription and Cellular Microcystin in Continuous Cultures of Microcystis aeruginosa PCC 7806

Abstract: Microcystins produced during harmful cyanobacterial blooms are a public health concern. Although patterns are emerging, the environmental cues that stimulate production of microcystin remain confusing, hindering our ability to predict fluctuations in bloom toxicity. In earlier work, growth at cool temperatures relative to optimum (18°C vs. 26°C) was confirmed to increase microcystin quota in batch cultures of Microcystis aeruginosa NIES-843. Here, we tested this response in M. aeruginosa PCC 7806 using continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 86 publications
2
21
0
Order By: Relevance
“…Microcystin concentrations were not different between treatments ( p -value > 0.1), nor were there differences in congener profile ( Supplementary Figure 1 ). This is in many ways not surprising as it was recently demonstrated that up-regulation of the genes associated with toxin synthesis in Microcystis can take 48 h to result in a measurable increase in toxin quota ( Martin et al, 2020 ). There was no significant change in chlorophyll a associated with nitrogen amendments, indicating that the phototroph biomass was not constrained by available nitrogen at the time of sampling.…”
Section: Discussionmentioning
confidence: 88%
“…Microcystin concentrations were not different between treatments ( p -value > 0.1), nor were there differences in congener profile ( Supplementary Figure 1 ). This is in many ways not surprising as it was recently demonstrated that up-regulation of the genes associated with toxin synthesis in Microcystis can take 48 h to result in a measurable increase in toxin quota ( Martin et al, 2020 ). There was no significant change in chlorophyll a associated with nitrogen amendments, indicating that the phototroph biomass was not constrained by available nitrogen at the time of sampling.…”
Section: Discussionmentioning
confidence: 88%
“…We have direct measurements of r by taking ln(final/initial cell density)/5 d. We obtained cell density values using the established linear relationship between fluorescence and particles/ml (from a FlowCam 5000, Flow Imaging Particle Analyzer, Fluid Imaging Technologies, Inc., Scarborough, ME, USA) for each nutrient condition for toxic M. aeruginosa and confirmed these relationships persisted over relevant timescales (Figure S6(a),(b)). Previous research has indicated the importance of temperature for influencing cell size (Martin et al 2020), while not considered in this study, could influence the relationship between density and biovolume. Finally, we assume negligible initial MC concentrations (τ 0 ≈ 0) and a loss rate of l = 0.09/day (given a half-life of 7 days reported by Zastepa et al 2014).…”
Section: Experiments 2: Thermal Acclimation and Cyanobacterial Toxin Productionmentioning
confidence: 92%
“…Encounter rates between viruses and hosts depend on virus and host densities (Murray and Jackson 1992), host cell size, and host motility (Wilhelm et al 1998). Host cell sizes (Atkinson, Ciotti and Montagnes 2003;Daufresne, Lengfellner and Sommer 2009;Martin et al 2020) and population densities Bernhardt, Sunday and O'Connor 2018) often decrease while motility increases (Crozier and Federighi 1924;Maeda et al 1976;Savage 2011, 2014;Gibert et al 2016) with temperature. Consequently, warming could have positive or negative effects on virus-host encounter rates, although more studies are needed (Table 1, Fig.…”
Section: Temperature Effects On Viruses and Viral Infectionsmentioning
confidence: 99%